Relationship between the product - market strategies and the performances of non-government Iranian non-oil exporters between 1994 to 1997. - hosein rahmanseresht; naaser sanobar (مطالعات مدیریت بهبود و تحول, 2004)
successful competition in the arena of global markets can be attributed to the functioning of governments and the funs' strategic orientations. Relatively considerable pieces of research hare been develod to the ways and means by which the Iranian governments can facilitate and encourage exports. But the effects the frims strategies, particularly exportstrategies, can have in boosting the exports of the country 's non-oil products hare been under researched. This second subject. therefore. is well worth exploring. rearrangement of machine and part components is required to [orm machine-part families. This process of rearrangement has been. considered as being subjective and difficult and may result in improper assignments to parts families, resulting in a negation of benefits promised. This paper presents an effective algorithm to identify part-families and bottleneck-parts, given machine groupings, rather than addressing the machine grouping problem in general